1999
DOI: 10.1038/sj.ijo.0800808
|View full text |Cite
|
Sign up to set email alerts
|

School performance and weight status of children and young adolescents in a transitional society in Thailand

Abstract: OBJECTIVE: To study the association between current or previous weight status and school performance among children and young adolescents of Hat Yai municipality, southern Thailand. DESIGN: Cross-sectional and longitudinal study SETTING: Primary and secondary schools of Hat Yai municipality, southern Thailand. SUBJECTS: 1207 grades 3 ± 6 and 587 grades 7 ± 9 students. MEASUREMENTS: Body mass index (BMI, kgam 2 ) calculated from weight and height measurement of subjects in 1992 and 1994; parental education leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
4
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 19 publications
9
85
4
8
Order By: Relevance
“…Low achievers at school are more likely to become obese, although it is not clear whether the poor performance leads to obesity or vice versa 150 .…”
Section: The School Environmentmentioning
confidence: 99%
“…Low achievers at school are more likely to become obese, although it is not clear whether the poor performance leads to obesity or vice versa 150 .…”
Section: The School Environmentmentioning
confidence: 99%
“…Although not a direct measure of intelligence, in one further prospective study school learning difficulties and poor performance in school exams were associated with a greater risk of being obese in young adulthood. 12 Three other prospective studies found that being overweight or obese in early childhood was associated with poor performance in school tests and assignments later in childhood, [13][14][15] though in one of these studies the association was attenuated to the null with adjustment for parental socioeconomic position. 13 In the Danish Military Survey the association between early life intelligence and later obesity attenuated to the null with adjustment for educational attainment and the authors concluded that education mediated the association between childhood intelligence and adult obesity.…”
Section: Introductionmentioning
confidence: 99%
“…3 Nonoverweight students demonstrated better grades relative to their overweight peers among sixth and seventh graders of Americans. 4 Similarly, Mo-suwan et al 5 found that an association between overweight status and poor school performance existed among Thai children from grades 7 --9. Mond et al 6 observed that the prevalence of impairment in gross motor skills was higher among obese than normal-weight boys, whereas the prevalence of impairment in the ability to focus attention was higher among the obese compared with normal-weight girls after controlling for age and other potential covariates among pre-school Germany children.…”
Section: Introductionmentioning
confidence: 99%